Magnetic, Dielectric, Electrical, Optical and Thermal Properties of Crystalline Materials (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
This Special Issue titled "Magnetic, Dielectric, Electrical, Optical and Thermal Properties of Crystalline Materials" is devoted to a general overview of the subject of crystalline materials and may extend to the nanocrystalline field. The articles related to the composition selection, the processing conditions optimization, and the structural and functional response. Thus, it includes synthesis, characterization, and application studies. Regarding the properties, their structure and mechanical, magnetic, dielectric, optical, and thermal properties investigations are the focus of interest.